Botanical insecticide–based nanosystems for the control of Aedes (Stegomyia) aegypti larvae - Duarte, Jonatas Lobato [UNESP]; Maciel de Faria Motta Oliveira, Anna Eliza; Pinto, Mara Cristina [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2020)
Aedes (Stegomyia) aegypti is a cosmopolitan species that transmits arbovirus of medical importance as dengue, Zika, and chikungunya. The main strategy employed for the control of this mosquito is the use of larvicidal agents. However, the overuse of synthetic chemical larvicides has led to an increase in resistant insects, making management difficult. Therefore, the use of botanical insecticide–based nanosystems as an alternative to the use of synthetic agents for the control of Ae. aegypti has gained more considerable attention in the last years, mainly due to the advantages of nanostructured delivery systems, such as (a) controlled release; (b) greater surface area; (c) improvement of biological activity; (d) protection of natural bioactive agents from the environment and thus achieving stability; and (e) lipophilic drugs are easier dispersed even in aqueous vehicles. This review summarizes the current knowledge about botanical insecticide–based nanosystems as larvicidal against Ae. aegypti larvae. The majority of papers used metallic nanoparticles (NPs) as larvicidal agents, mainly silver nanoparticles (AgNPs), showing potential for their use as an alternative, followed by nanoemulsions containing vegetable oils, most essential oils, nanosystems that allow the dispersion of this high hydrophobic product in water, the environment of larval development. The final section describes scientific findings about the mode of action of these NPs, showing the gap about this subject in literature.
Keywords: Arboviruses; Metallic nanoparticles; Nanoemulsions; Nanotechnology; Natural products